Citizen science for hydrological risk reduction and resilience building. (24th October 2017) - Paul, Jonathan D.; Buytaert, Wouter; Allen, Simon; Ballesteros‐Cánovas, Juan A.; Bhusal, Jagat; Cieslik, Katarzyna; Clark, Julian; Dugar, Sumit; Hannah, David M.; Stoffel, Markus; Dewulf, Art; Dhital, Megh R.; et al.
Abstract : In disaster risk management (DRM), an emerging shift has been noted from broad‐scale, top‐down assessments toward more participatory, community‐based, bottom‐up approaches. Arguably, nonscientist local stakeholders have always played an important role in knowledge risk management and resilience building within a hydrological context, such as flood response and drought alleviation. However, rapidly developing information and communication technologies such as the Internet, smartphones, and social media have already demonstrated their sizeable potential to make knowledge creation more multidirectional, decentralized, diverse, and inclusive. Combined with technologies for robust and low‐cost sensor networks, a 'citizen science' approach has recently emerged as a promising direction in the provision of extensive, real‐time information for risk management. Such projects work best when there is community buy‐in, when their purpose(s) are clearly defined at the outset, and when the motivations and skillsets of all participants and stakeholders are well understood. They have great potential to enhance knowledge creation, not only for data collection, but also for analysis or interpretation. In addition, they can serve as a means of educating and empowering communities and stakeholders that are bypassed by more traditional knowledge generation processes. Here, we review the state‐of‐the‐art of citizen science within the context of hydrological risk reduction and resilience building. Particularly when embedded within a polycentric approach toward risk governance, we argue that citizen science could complement more traditional knowledge generation practices, and also enhance innovation, adaptation, multidirectional information provision, risk management, and local resilience building. WIREs Water 2018, 5:e1262. doi: 10.1002/wat2.1262 This article is categorized under: Engineering Water > Planning Water Science of Water > Water Extremes Abstract : Conceptual overview of the paper: potential opportunities of citizen science‐related concepts and technologies in the context of knowledge generation for hydrological risk reduction and resilience building.